Dentatin isolated from Clausena excavata induces apoptosis in MCF-7 cellsthrough the intrinsic pathway with involvement of NF-kB signalling andG0/G1 cell cycle arrest : a bioassay-guided approach - Arbab, Ismail Adam; Abdul, Ahmad Bustamam; Sukari, Mohd Aspollah; Abdullah, Rasedee; Syam, Suvitha; Kamalidehghan, Behnam; Ibrahim, Mohamed Yousif; Elhassan Taha, Manal Mohamed; Abdelwahab, Siddig Ibrahim; Mohd Ali, Hapipah; Mohan, Syam (Elsevier, 2013)
Ethnopharmacological relevance: Clausena excavata Burm. f. has been used in folk medicines in eastern Thailand for the treatment of cancer. Materials and methods: To investigate the apoptosis mechanism, we isolated dentatin (DTN) from this plant using a bioassay-guided approach. DTN-induced cytotoxicity was observed with the MTT assay. Acridine orange/propidium iodide staining was used to detect cells in early apoptosis and high content screening (HCS) to observe nuclear condensation, cell permeability, mitochondrial membrane potential (MMP) and cytochrome c release. Apoptosis was conﬁrmed with a clonogenic assay, DNA laddering and caspase 3/7 and 9 assays. Reactive oxygen species (ROS) formation, Bcl-2 and Bax expression, and cell cycle arrest were also investigated. The involvement of nuclear factor-kappa B (NF-kB) was analysed with the HCS assay. Results: A signiﬁcant increase in chromatin condensation in the cell nucleus was observed by ﬂuorescence analysis. Apoptosis was conﬁrmed by the reduced number of colonies in the clonogenic assay and the increased number of cellular DNA breaks in treated cells observed as a DNA ladder. Treatment of MCF-7 cells with DTN encouraged apoptosis with cell death-transducing signals that reduced MMP by down-regulation of Bcl-2 and up-regulation of Bax, triggering cytochrome c release from the mitochondria to the cytosol. The released cytochrome c triggered the activation of caspase 9 followed by the executioner caspase 3/7. DTN treatment signiﬁcantly arrested MCF-7 cells at the G0/G1 phase (po0.05) and ROS was signiﬁcantly elevated. Moreover, DTN signiﬁcantly blocked the induced translocation of NF-kB from cytoplasm to nucleus. Conclusion: Together, the results demonstrated that the DTN isolated from Clausena excavata inhibited the proliferation of MCF-7 cells, leading to cell cycle arrest and programmed cell death, which was conﬁrmed to occur through the mitochondrial pathway with involvement of the NF-kB signalling pathway.